PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT CAHAYA KANDIL JAGAT RAYA MOJOKERTO - Rahayu Ningsih, Tiyas (Universitas Nusantara PGRI Kediri, 2023)
Purposeful research (1) Work discipline has a substantial effect on the performance of PT Cahaya Kandil Jagat Raya Mojokerto personnel, according to this study. (2) Work motivation has a significant impact on PT Cahaya Kandil Jagat Raya Mojokerto employees' work performance. (3) Job satisfaction has a substantial impact on PT Cahaya Kandil Jagat Raya Mojokerto employees' performance. (4) At the same time, discipline work, motivation and satisfaction happiness all have a substantial impact on PT Cahaya Kandil Jagat Raya Mojokerto employees' work results. This study's population belonging PT Cahaya Kandil Jagat Raya Mojokerto employees. To use population sampling, this study has 40 participants. And multiple linear regression was used to examine the data using the SPSS Version 29 tool. (1) Partial work discipline has a significant influence the effect on the performance PT Cahaya Kandil Jagat Raya personnel, according to the findings of this study. Mojokerto. (2) Work motivation has a major influence on PT Cahaya Kandil Jagat Raya Mojokerto employees' work performance. (3) Partially satisfied staff at PT Cahaya Kandil Jagat Raya Mojokerto perform significantly better. (4) At the same time, work discipline, motivation, and job happiness all have a substantial impact on PT Cahaya Kandil Jagat Raya Mojokerto employees' work results.